Regional selective construction of nano-Au on Fe3O4@SiO2@PEI nanoparticles by photoreduction. (15th April 2016) - Zhou, Ying; Ping, Tuo; Maitlo, Inamullah; Wang, Bowen; Akram, Muhammad Yasir; Nie, Jun; Zhu, Xiaoqun
Abstract: A magnetically separatable catalyst Fe3 O4 @SiO2 @PEI@Au (gold) nanoparticle was successfully constructed by a novel regional selective photoreduction method. Based on the photolysis mechanism of a type II photoinitiator, through controlling the distribution of polyethylene imine (PEI), Au nanoparticles about 10 nm, which are only on the surface of the Fe3 O4 @SiO2 @PEI nanoparticle, could be photoreduced due to the PEI acting as a coordinating agent, capping agent, and photoreducing agent simultaneously. The small size Au nanoparticles endow the catalyst with a high catalytic performance toward the reduction of 4-nitroaniline to 4-aminophenol by NaBH4 . In addition, magnetic Fe3 O4 @SiO2 @PEI@Au nanoparticles could easily be recovered and could be reused at least six times still keeping catalytic efficiency higher than 95%, which contributes to their high stability and magnetization. Furthermore, compared to another reported approach, this method showed great regional selectivity of reducing metal nanoparticles by controlling the distribution of the PEI. Taking advantage of the regional selectivity of the photoreducing method could also be used to fabricate other metal nanoparticles as catalysts for various reactions.